PID Designs Using DE and PSO Algorithms for Damping Oscillations in a DC Motor Speed - Lailis Syafaah; Widianto Widianto; Ilham Pakaya; Diding Suhardi; M. Irfan (IAES Indonesia Section, 2017)
In this paper, a design and a simulation of a PID controller are presented to control a DC motor speed. The design is proposed to increase a dynamic stability of the motor speed. Changing the speed setpoint values may generate oscillations, thus the controller is required to maintain a system stability. The PID controller is tuned using Differential Evolutionary (DE) and Particle Swarm Optimization (PSO) algorithms. Performance of both algorithms is compared by Integral Square Error (ISE) and rise time values. Experiments are performed by changing the speed setpoint values. In simulation results, the ISE and the rise time values of the DE algorithm are slower than the PSO algorithm.